PENGARUH STRUKTUR KEPEMILIKAN KELUARGA TERHADAP KINERJA PERUSAHAAN PADA SEKTOR PERTANIAN - Pannya Pannya Pannya; Juniarti Juniarti Juniarti (Business Accounting Review, 2017)
Research of the influence of family ownership on firm performance in agricultural sector has not been researched yet. However, researches on the affect of family ownership on firm performance had been widely studied before. This study aimed to investigate the influence of family ownership on firm performance in companies engaged in agriculture sector. The family ownership was measured based on a 10% control limit, or the presence of family members on the board. There were three control variables used in this research, namely Good Corporate Governance (GCG), intensity rivalry and negative earning. This study was conducted on companies engaged in the agricultural sector in Indonesia from 2010 to 2015 with a sample size of 21 companies. The result of the research showed that there was no influence of family ownership on firm performance. The control variable GCG had negative affect to firm performance, intensity rivalry had positive affect to firm performance, while negative earning had negative affect to firm performance.